Efektivitas Kepemimpinan Transformasional Terhadap Peningkatan Kinerja Perawat - Fitriyanti Patarru'; Nursalam Nursalam; Eka Mishbahatul Mar’ah HAS (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Transformational leadership is a style of leadership that motivates subordinates to work towards organizational goals. Objective: To determine the effectiveness of transformational leadership on nurse performance. Method: The database used in this study were Scopus, SAGE and Pubmed were limited to the last 5 years of publication from 2016 to 2020, full-text articles and in English. The keyword used were "Transformational Leadership" AND "Performance AND “Nursing". This systematic review used 15 articles that fit the inclusion criteria. Results: transformational leadership effect improved nurse performance in providing health and patient safety services because it could increase work motivation, well-being, work creativity, work performance, teamwork, organizational commitment, organizational climate, job satisfaction and reduce nurses' stress levels in work so turnover rate decreases. Transformational leadership, if implemented could have a positive impact on the quality of health services that could provide satisfaction to patients. Conclusion: Transformational leadership has a lot of effectiveness in improving nurse performance in hospitals. Suggestion: Transformational leadership style models are considered necessary to be applied by leaders in hospitals in Indonesia. Keywords: transformational leadership; performance; nursing ABSTRAK Latar belakang: Kepemimpinan transformasional merupakan gaya kepemimpinan yang memotivasi para bawahan agar bekerja untuk mencapai tujuan organisasi. Tujuan: Untuk mengetahui efektivitas kepemimpinan transformasional terhadap kinerja perawat. Metode: Database yang digunakan dalam penelitian ini adalah Scopus, SAGE dan Pubmed terbatas untuk publikasi 5 tahun terakhir dari 2016 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “Transformational Leadrship” AND “Performance AND “Nursing”. Systematic review ini menggunakan 15 artikel yang sesuai dengan kriteria inklusi. Hasil: kepemimpinan transformasional memiliki efektivitas pada peningkatan kinerja perawat dalam memberikan pelayanan kesehatan dan keselamatan pasien karena dapat meningkatkan motivasi kerja, kesejahteraan, kreativitas kerja, prestasi kerja, kerjasama tim, komitmen organisasi, iklim organisasi, kepuasan kerja dan menurunkan tingkat stress perawat dalam bekerja sehingga tingkat turn over berkurang. Kepemimpinan transformasional jika diterapkan dapat memberi dampak positif bagi kualitas mutu pelayanan kesehatan yang dapat memberi kepuasan kepada pasien. Simpulan: Kepemimpinan transformasional memiliki banyak efektivitas dalam meningkatkan kinerja perawat di rumah sakit Saran: Model gaya kepemimpinan transformasional dipandang perlu untuk diterapkan oleh para pemimpin di rumah sakit yang ada di Indonesia. Kata kunci: kepemimpinan transformasional; kinerja; perawat